MANFAAT REFORMASI AGRARIA BAGI PEMENUHANHAK-HAK ASASI PETANI - Pristi Suhendro L (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2013)
After the end of the Cold War caused the collapse of the socialist countries, the ideas and policies ofliberalization, privatization and modernization became the dominant current of thought.The rise of theneo-liberals have created an atmosphere that was not conducive to the idea of Agrarian Reform (RA).Anexample is the rampant land disputes that human casualties.The dispute occurred in almost all areasand involves almost all sectors.Based on reports BPKPA (2000), at least 1742 cases recorded as landdisputes in Indonesia, the largest in the 25 provinces.Then the dispute was followed by 12 cases ofabduction, 24 cases of murder, 39 cases of shootings, 151 terror cases, 163 cases of torture, 212 cases ofintimidation, and 763 arrests.Agrarian condition at some time in fact a product of the operation of fourinteracting factors, namely: (a) historical legacy, (b) internal dynamics, (c) government interventionthrough its policies, and (d) external intervention such as, large private companies both domestic andforeign, the movement of the "Transational Corporation" (TNC), the fund provider agencies.AgrarianReform should be "Sustainable", namely:First: Agrarian Reform policy must consider environmentalsustainability. In this context, techno-farming or a subordinate part of the eco-farming.The land mustnot be distributed marginal lands that can only be productive in the short and prone to erosion.Preciselyfor the rights of generations to come, it would require conservation of resources, namely foodproduction: soil, water, and biodiversity.Second, from the socio-political aspects, sustainability AgrarianReform requires two things: a.AgrarianReform should not be discriminatory.Rural women should beinvolved role.B.Need to be created and maintained a democratic atmosphere that ensures the existenceof association, and the strengthening of farmer organizations.Agrarian Reform is a big agenda butfundamental.Therefore, the necessary co-operation between the various parties, especially "those whoare in favor of the interests of the people, centered on small farmers and farm workers and those whowant to unite in the struggle for agrarian reform in order to materialize into reality.